Long intergenic noncoding RNA 299 methylation in peripheral blood is a biomarker for triple-negative breast cancer - Lorenzo Bermejo, Justo; Hamann, Ute; Hoheisel, Jörg D.; Garcia Mesa, Karen; González Silos, Rosa (Epigenomics, 2019)
Aim: To identify DNA methylation biomarkers in peripheral blood samples from triple-negative breast cancer (TNBC) patients. Materials & methods: We conducted an epigenome-wide association study (EWAS): the most promising markers were identified in 233 TNBC case–control pairs (discovery set) and subsequently validated in an independent validation set (57 TNBC patients and 124 controls). Results: cg06588802 (LINC00299/ID2) showed a higher methylation in TNBC patients compared with controls (discovery set: 3% increase, p-value = 0.0009; validation set: 2% increase, p-value = 0.01). Consistent results at four neighboring methylation probes and the strong negative correlation (rho = -0.93) with LINC00299 expression add plausibility to this result. Conclusion: Hypermethylation of LINC00299 in peripheral blood may constitute a useful circulating biomarker for TNBC.
Published online 13 September 2018
Gesehen am 19.07.2019